Tenogenically Induced Allogeneic Mesenchymal Stem Cells for the Treatment of Proximal Suspensory Ligament Desmitis in a Horse - Vandenberghe, Aurélie; Broeckx, Sarah Y.; Beerts, Charlotte; Seys, Bert; Zimmerman, Marieke; Verweire, Ineke; Suls, Marc; Spaas, Jan H. (Frontiers in Veterinary Science, 2015)
Suspensory ligament injuries are a common injury in sport horses, especially in competing dressage horses. Because of the poor healing of chronic recalcitrant tendon injuries, this represents a major problem in the rehabilitation of sport horses and often compromises the return to the initial performance level. Stem cells are considered as a novel treatment for different pathologies in horses and humans. Autologous mesenchymal stem cells (MSCs) are well known for their use in the treatment of tendinopathies, however, recent studies report a safe use of allogeneic MSCs for different orthopaedic applications in horses. Moreover, it has been reported that predifferentiation of MSCs prior to injection might result in improved clinical outcomes. For all these reasons, the present case report describes the use of allogeneic tenogenically induced peripheral blood-derived MSCs for the treatment of a proximal suspensory ligament injury. During conservative management for 4 months, the horse demonstrated no improvement of a right front lameness with a Grade 2/5 on the AAEP scale and a clear hypo-echoic area detectable in 30% of the cross sectional area. From 4 weeks after treatment, the lameness reduced to an AAEP Grade 1/5 and a clear filling of the lesion could be noticed on ultrasound. At 12 weeks (T4) after the first injection, a second intralesional injection with allogeneic tenogenically induced MSCs and PRP was given and at 4 weeks after the second injection (T5), the horse trotted sound under all circumstances with a close to total fiber alignment. The horse went back to previous performance level at 32 weeks after the first regenerative therapy and is currently still doing so (i.e. 20 weeks later or 1 year after the first stem cell treatment). In conclusion, the present case report demonstrated a positive evolution of proximal suspensory ligament desmitis after treatment with allogeneic tenogenically induced MSCs.